2022
DOI: 10.1038/s41598-022-23646-3
|View full text |Cite|
|
Sign up to set email alerts
|

Single-nucleus transcriptomics of IDH1- and TP53-mutant glioma stem cells displays diversified commitment on invasive cancer progenitors

Abstract: Glioma is a devastating brain tumor with a high mortality rate attributed to the glioma stem cells (GSCs) possessing high plasticity. Marker mutations in isocitrate dehydrogenase type 1 (IDH1) and tumor protein 53 (TP53) are frequent in gliomas and impact the cell fate decisions. Understanding the GSC heterogeneity within IDH1- and TP53- mutant tumors may elucidate possible treatment targets. Here, we performed single-nucleus transcriptomics of mutant and wild-type glioma samples sorted for Sox2 stem cell mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…The following datasets were accessed: GSE84465 36 , GSE131928 37 , GSE164624 38 , GSE151506 39 and GSE117891 40 . The counts data from each dataset was used to reassign cell types using scSorter 41 with the following markers used to identify Neoplastic (e.g.…”
Section: Single Cell Sequencing Analysis Using Merged Dataset Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…The following datasets were accessed: GSE84465 36 , GSE131928 37 , GSE164624 38 , GSE151506 39 and GSE117891 40 . The counts data from each dataset was used to reassign cell types using scSorter 41 with the following markers used to identify Neoplastic (e.g.…”
Section: Single Cell Sequencing Analysis Using Merged Dataset Librarymentioning
confidence: 99%
“…FOXM1) induced by chemotherapy 50 . Here, we merged several single cell RNA sequencing datasets (GSE84465 36 , GSE131928 37 , GSE164624 38 , GSE151506 39 and GSE117891 40 ) into a library comprising of samples with different grades, IDH1 mutation status and other features to perform hdWGCNA analysis. The UMAP following harmonization shows clear separation of distinct cell types (Fig.…”
Section: Genetic Module (Gm-1) With High Lonp1 Expression Exhibits Wn...mentioning
confidence: 99%
“…Glioma stem cells exhibit an increased level of CD44 [ 45 ]. In addition to that, our recent data, obtained by single nucleus transcriptomics of glioma stem cells captured from tumor samples by sorting for Sox2 positive nuclei, demonstrated that IDH1 R132H migrating astrocyte-precursor cells are characterized by the highest CD44 expression among different subpopulations of glioma stem cells [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to determine nanomechanical profiles that are characteristic for the investigated cell phenotypes. The increased stiffness and Young’s modulus of the IDH1 R132H mutant cells turned out to be highly indicative, which is probably mediated by both altered cytoskeleton and lipogenesis in mutant cells [ 24 , 46 , 61 ]. In this work, we first used the early-passage glioma cell cultures to compare hardness of IDH1 R132H mutant and IDH1 wild-type cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our study illustrated that patients with glioma in the two risk groups had distinct genetic alterations, activated pathways, and potentially sensitive drugs. A common characteristic of gliomas is the presence of markers for IDH1 and TP53 mutations, which influence the fate of the cells ( 42 ). The two risk groups were IDH1- and TP53-dominant mutations, respectively, suggesting discrepant oncogenesis mechanisms.…”
Section: Discussionmentioning
confidence: 99%